FORMULASI SALEP EKSTRAK ETANOLIK DAUN BINAHONG (Anrederacordifolia (Ten.) Steenis) DENGAN VARIASI BASIS SALEP - Elya Zulfa; Tegar Bagus Prasetyo; Mimik Murukmihadi (Universitas Wahid Hasyim Semarang, 2015)
ABSTRACT The absorbtion-based ointment of ethanolic extract of binahong leaves (Anredera cordifolia (Ten.) Steenis) on 10% concentrate has antibacterial activity towards Staphylococcus aureus. In order to improve the activity of this ethanolic extract of binahong leaves, it is necessarily to adjust the ointment’s base of formulation. The aims of study are to determine the ointment’s physical characteristics which various base such as hydrocarbon, absorbtion and water solubility. The ethanolic extract of binahong leaves obtained from maceration method, using 70% of ethanol. The ointment was made based on the variation of its base which are hydrocarbon, absorbtion and water solubility. The obtained oinment then was examined on its physical characteristics properties including organoleptic test, pH, viscosity, stickiness, spreadability, and antibacterial activity toward Staphylococcus aureus on the agar plate medium. The organoleptic and pH test result data were analyzed descriptively. The data of stickiness, viscosity were analyzed using one-way ANOVA and Tukey with the level of confidence up to 95%, whilst the spreadability data was analyzed using Kruskal wallis and Man whitney. There were significant differences between the results of viscosity, stickiness, on each formula of ethanolic extract ointment of binahong leaves. However, there were no significant differences on the pshycal characteristic of the pH, organoleptic, homogenic, and spreadability. Keywords: Ointment, Binahong leaves, Antibacterial activity, Staphylococcus aureus.